Does a “Blue Revolution” help the poor? Evidence from Bangladesh - Rashid, Shahidur; Minot, Nicholas; Lemma, Solomon (Wiley, 2019)
The rapid growth in aquaculture production, globally and in Bangladesh is well documented. Over 2000–2010, per capita production of aquaculture grew 76%, while the consumer price of fish declined 45%. Previous studies have suggested pro-poor effects of aquaculture based on fish production and consumption patterns. This study attempts to quantify the contribution of aquaculture to income growth and poverty reduction in Bangladesh, using household survey data and a microsimulation approach based on an expanded version of Deaton's concept of net benefit ratio. We estimate that aquaculture's contribution to income growth between 2000 and 2010 was 2.1%, including both price and quantity effects. This income growth was translated into poverty reduction of 1.7 percentage points. Although these estimates seem small, they represent almost 10% of the overall poverty reduction in Bangladesh during the first decade of the 21st century. Put differently, of the 18 million Bengalis who escaped poverty during 2000–2010, about 1.8 million of them managed to do so because of the rapid growth in aquaculture, which contributed to rural income while making fish more accessible to consumers.